2017
DOI: 10.1111/ijd.13726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relation between lipid coat, transepidermal water loss, and skin pH

Abstract: In the T-zone, a thinner lipid coat resulted in relatively high TEWL and pH levels changing toward alkaline. In the U-zone, thinner lipid coat was accompanied by lower TEWL and pH changing toward alkaline. We also observed that lower values of lipid coat up to 100 μg/cm were associated with higher pH values ranging toward the basic character pH 5.6-9.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
(61 reference statements)
0
20
0
Order By: Relevance
“…estimated that the average pH of uncoated nail plates was 5.0 ± 0.5. These studies indicate that the acidic pH is very important for maintaining regular microbiome …”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…estimated that the average pH of uncoated nail plates was 5.0 ± 0.5. These studies indicate that the acidic pH is very important for maintaining regular microbiome …”
Section: Resultsmentioning
confidence: 85%
“…The acidic pH of the skin and nails within the range between 4.0 and 5.6 protects them from harmful exogenous factors . Factors affecting the skin and nails also exert an impact on pH values . Another important element is perspiration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it may be concluded that the use of a gel polish hybrid causes an increase in pH, which predisposes to various infections, while the acidic pH of nails in the range from 4.0 to 5.6 protects them from harmful exogenous agents. Factors affecting the skin and nails also have an impact on pH values …”
Section: Discussionmentioning
confidence: 99%
“…The measurement is carried out by calculating the density gradient between the sensors. By registering the difference in water vapor density, we determined the TEWL value expressed in units: g/m 2 /h …”
Section: Methodsmentioning
confidence: 99%